Influence of Microbial Treatments on Vine Growth and Must Quality: Preliminary Results - Nicola Mercanti; Monica Macaluso; Ylenia Pieracci; Leonardo Bertonelli; Guido Flamini; Angela Zinnai (Plants)
Microorganisms play a crucial role in addressing the challenges related to the increasing detrimental effects of intensive agriculture in vineyards by contributing to various aspects, from maintaining soil health and vine vitality to influencing fermentation and the overall wine features. Among microorganisms, mycorrhizal fungi are widely distributed in both natural and agricultural ecosystems, and their mutually beneficial relationship with most terrestrial plants provides valuable ecological benefits. Nowadays, the wine industry is increasingly moving toward the production of organic wines, highlighting the need for novel and healthier strategies that prioritize both the consumer well-being and the quality of the final wine product. Following our previous study in collaboration with the Bioma SA Company (Quartino, Switzerland), the investigation was continued by extending the organic practice to the cultivation. The present work, indeed, aimed to evaluate the influence of the treatment with mycorrhizal fungi on the metabolism of “Sangiovese” grapevines. In particular, the chemical parameters, including alcohol content, pH, acidity, phenolic composition, and sulfur dioxide, were assessed on the must, while the analysis of the volatile emission was conducted both on whole and pressed grapes, on must, as well as on the grape skins. To the best of our knowledge, this is the first study investigating the mycorrhizal fungi association effect on the quality of “Sangiovese” grapes and, further, its effect on the VOCs emission.